PRINCIPLES AND METHODS OF OPTIMIZATION EDUCATIONAL PROCESS IN LESSONS ON LABOR EDUCATION IN SECONDARY SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
In the article basic principles and methods of optimization of teaching of labour stud are considered at general school on the basis uf the methodical reasonings and research of their essence. To optimize the offered concrete ways educational process with the purpose of capture by a teacher by the certain methads of optimiza tion, which will stipulate the inprovement of educational-educate work.
Keywords: principles and methods of optimization; educational-educate process; labour study; creative approach; pedagogical trade